Impact of lanadelumab on health‐related quality of life in patients with hereditary angioedema in the HELP study. Issue 4 (24th December 2020) - Lumry, William R.; Weller, Karsten; Magerl, Markus; Banerji, Aleena; Longhurst, Hilary J.; Riedl, Marc A.; Lewis, Hannah B.; Lu, Peng; Devercelli, Giovanna; Jain, Gagan; Maurer, Marcus; ,
Abstract: Background: An objective of the phase 3 HELP Study was to investigate the effect of lanadelumab on health‐related quality of life (HRQoL) in patients with hereditary angioedema (HAE). Methods: Patients with HAE‐1/2 received either lanadelumab 150 mg every 4 weeks (q4wks; n  = 28), 300 mg q4wks ( n  = 29), 300 mg every 2 weeks (q2wks; n  = 27), or placebo ( n  = 41) for 26 weeks (days 0–182). The Angioedema Quality of Life Questionnaire (AE‐QoL) was administered monthly, consisting of four domain (functioning, fatigue/mood, fears/shame, nutrition) and total scores. The generic EQ‐5D‐5L questionnaire was administered on days 0, 98, and 182. Comparisons were made between placebo and (a) all lanadelumab‐treated patients and (b) individual lanadelumab groups for changes in scores (day 0–182) and proportions achieving the minimal clinically important difference (MCID, −6) in AE‐QoL total score. Results: Compared with the placebo group, the lanadelumab total group demonstrated significantly greater improvements in AE‐QoL total and domain scores (mean change, −13.0 to −29.3; p  < 0.05 for all); the largest improvement was in functioning. A significantly greater proportion of the lanadelumab total group achieved the MCID (70% vs 37%; p  = 0.001). The lanadelumab 300 mg q2wks group had the highest proportion (81%; p  = 0.001) and was 7.2 times more likely to achieve the MCID than the placebo group. Mean EQ‐5D‐5L scores at day 0 were high in all groups, indicating low impairment, with no significant changes at day 182. Conclusion: Patients with HAE‐1/2 experienced significant and clinically meaningful improvements in HRQoL measured by AE‐QoL following lanadelumab treatment in the HELP Study. Abstract : In the phase 3 HELP Study, HRQoL (health‐related quality of life) of patients with HAE (hereditary angioedema)‐1/2 was evaluated using the angioedema‐specific AE‐QoL (Angioedema Quality of Life Questionnaire). After 26 weeks, lanadelumab‐treated patients experienced significantly greater HRQoL improvements than placebo‐treated patients. Patients receiving lanadelumab 300 mg q2wks (every 2 weeks) were most likely to see clinically meaningful benefit, with 81% reaching the MCID (minimal clinically important difference) and seven times greater odds vs placebo for this achievement. Abbreviations: AE‐QoL, Angioedema Quality of Life Questionnaire; HAE, hereditary angioedema; HRQoL, health‐related quality of life; MCID, minimal clinically important difference; q2wks, every 2 weeks; q4wks, every 4 weeks.